Performance analysis of modulation diversity with OSTBC transmission over Nakagami-m fading channels - Yilmaz, Ahmet; Kucur, Oğuz (Elsevier Gmbh, 2014)
In this paper performance of modulation diversity with multiple-input multiple-output transmission is studied over flat Nakagami-m fading channels with arbitrary fading parameter m. In the system, orthogonal space-time block coding and maximal ratio combining like combiner are used for transmission and reception, respectively. Exact pairwise error probability expression is derived to observe performance of the system. Moreover, in order to obtain the diversity order of the system, asymptotic pairwise error probability expression is also derived. Optimum rotation angles are analytically obtained for binary and quadrature phase shift keying modulations. Theoretical results are validated by Monte Carlo simulations. (C) 2013 Elsevier GmbH. All rights reserved.
Keywords: Signal space diversity; Orthogonal space-time block coding; Maximal ratio combining; Nakagami-m fading; Rotated constellation